A comunicação e as experiências do feedback entre empreendedores e seus parceiros - Dellaquila, Alessandra Cassia de Medeiros (2023)
Brazilian Micro and Small Enterprises have great relevance in the economic and social scenario, representing 98% of businesses, with more than 17.5 million enterprises existing in the country, which generate approximately 30% of GDP and 44.8% of formal jobs. Given the relevance of this segment for Brazilian economy, communication among entrepreneurs and their partners has become an important construct to be analyzed, through feedback experiences, with the aim of researching how they can contribute for improving businesses. The overall objective of this project was: to analyze how communication supported by feedback takes place between entrepreneurs and their partners. The research was qualitative, descriptive in nature, and had the entrepreneurs, agents and the manager of SEBRAE’s Local Agents of Innovation program as unit of analysis. The development of data collection was carried out in two stages: the first one, by carrying out a systematic review on the term feedback in entrepreneurial contexts, and the second one, by conducting interviews, starting with the entrepreneurs, followed by the agents and, finally, with the manager. After data collection, these data were transcribed in full, in order to facilitate the analysis of the results therefrom. The results were organized by using the software Atlas.ti – used, as it is a software specialized in qualitative research, in the categorization and treatment of results, through content analysis. Such results corroborate the theories supporting this research, showing that seeking feedback is important to improve the performance, besides both positive and negative feedbacks contribute not only to the business, but also, above all, to personal growth and learning, through interpersonal relationships with agents. Trust is the basis of the communication process and there is no good quality relationship without it. Another important finding is that both the affective and cognitive aspects are present in all processes of relational exchange among entrepreneurs and agents, except that one has more emphasis at some times than the other one. The study brought important contributions by identifying the recurrence of some feedback processes in entrepreneurial communication, namely, Feedback Seeking, Feedback Effect, Positive and Negative Feedback and Performance Feedback, as well as the relational and cyclical character among them.